Upaya Mengatasi Bullying Melalui Pendekatan Rebt (Rational Emotive Behavior Therapy) Terhadap Siswa MTS Kaliwining Rambipuji - Zahroa, Nadia Nuris; Zakiyah, Naili Ziana; Fatmawati, Fatmawati; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2022)
This research is an effort to overcome bullying by students of MTS Kaliwining Rambipuji. The background of this research is the occurrence of cases of verbal and non-verbal bullying that can harm students and the efforts of accompanying teachers to deal with conflicts with the REBT (Rational Emotive Behavior Therapy) approach. This research was conducted to find out how big the level of bullying that occurred at MTS Kaliwining Rambipuji. This qualitative descriptive research is used as a theory of development that has been built from data obtained in the field or research location. The informants in the study were accompanying teachers and 6 students who were victims of bullying at MTS Kaliwining Rambipuji. Data collection techniques used observation and interviews, while the research results obtained were bullying caused by student backgrounds and toxic friendships. The handling efforts carried out by the accompanying teacher are by giving reprimands, coaching, calling parents.